3D printing polylactic acid polymer-bioactive glass loaded with bone cement for bone defect in weight-bearing area - Ding, Yurun; Liu, Xiaolin; Zhang, Jue; Lv, Zhuocheng; Meng, Xiangchao; Yuan, Zhiguo; Long, Teng; Wang, You (Frontiers in Bioengineering and Biotechnology, 2022)
The treatment of bone defect in weight-bearing area is mainly to transplant filling materials into the defect area, for the purpose of providing immediate and strong support for weight-bearing. At present, the commonly used filling material is bone cement, which can only provide physical support without bone regeneration effect. The long-term stress at the interface may cause loosening of bone cement. The ideal filling material should provide not only strong mechanical support, but also promote bone regeneration. We introduce 3D printing frame-filling structure in this study. The structure was printed by polylactic acid/bioactive glass as the frame, and bone cement as the filler. In this system, bone cement was used to provide immediate fixation, and the frame provided long-term fixation by promoting osteogenic induction and conduction between the interface. The results showed that the degradation of bioactive glass in the frame promoted osteogenic metabolism, induced M2 polarization of macrophages, inhibited local inflammatory response. The in vivo study revealed that implantation of the frame-filling structure significantly promoted bone regeneration in femoral bone defect area of New Zealand white rabbits. For bone defect in weight-bearing area, long-term stability could be obtained by bone integration through this frame-filling structure.